Efeitos do Tai Chi Chuan na qualidade de vida, flexibilidade e equilíbrio de idosos - Rodrigues Júnior, Arnaldo [UNESP]; Navega, Marcelo Tavella [UNESP] (My University, 2010)
Introduction: The growth of the aged population in developing countries is fast. Cognitive, motion, metabolic and social injuries are associated to aging, which are potentially able to impair the quality of life of the elder population. A physical activity that provides a mental and physical welfare besides its importance to the good aging, therefore, the Tai Chi Chuan is considered an effi cient and cheap way to improve the quality of life and to reduce the physical alterations unchained by aging. Objective: To verify the effect of the Tai Chi Chuan of the quality of life, fl exibility and balance in elderly. Methods: Nine volunteers, three men (66.33 ± 13.32 years) and six women (68.67 ± 11.34 years) participated in the study. They performed the training of Tai Chi Chuan during 12 weeks, two times per week, with duration of one hour each session. The volunteers were evaluated at the beginning of the study and after the 12 weeks of training by means of the application of the questionnaire of quality of life SF-36, a scale of balance and the test to seat and to reach was applied to evaluate the fl exibility. Results: It was observed in the Tai Chi Chuan training improvement of the balance and fl exibility; however, the quality of life did not present signifi cant difference. Conclusion: These fi ndings allow us to conclude that the Tai Chi Chuan was effi cient in the improvement of the equilibrium and the fl exibility of elder people; however, it did not modify the Quality of Life of the studied population.

Introdução: É acelerado o crescimento da população idosa em países em desenvolvimento. Ao envelhecimento estão associadas perdas cognitivas, metabólicas, neuromotoras e sociais potencialmente capazes de comprometer a qualidade de vida da pessoa idosa. Uma atividade física que proporcione um bem estar físico e mental é fundamental para o bom envelhecimento, sendo, portanto o Tai Chi Chuan uma forma efi caz e barata para melhorar a qualidade de vida e reduzir as alterações físicas desencadeadas pelo envelhecimento. Objetivo: Verifi car os efeitos do Tai Chi Chuan na Qualidade de Vida, fl exibilidade e equilíbrio de idosos. Método: Participaram do estudo nove voluntários, três homens (66,33 ± 13,32 anos) e seis mulheres (68,67 ± 11,34 anos) que realizaram o treinamento de Tai Chi Chuan durante 12 semanas, duas vezes por semana, com duração de uma hora cada sessão. Os voluntários foram avaliados no início e após as 12 semanas de treinamento por meio da aplicação do questionário de qualidade de vida SF-36, de uma escala de equilíbrio e pelo teste de sentar e alcançar para avaliação da fl exibilidade. Resultados: Com o treinamento de Tai Chi Chuan foi observado melhora no equilíbrio e na fl exibilidade, porém a qualidade de vida não apresentou diferença signifi cativa. Conclusão: Os dados obtidos permitem concluir que o Tai Chi Chuan foi efi caz na melhora do equilíbrio e da fl exibilidade de pessoas idosas, entretanto não alterou a Qualidade de Vida dos participantes.
Effects of the Tai Chi Chuan of the quality of life, flexibility and balance in elderly
Keywords: equilibrio; Flexibilidade; idoso; Tai Chi Chuan